Civic space/cyberspace the American public library in the information age - Molz, Redmond Kathleen, 1928- (MIT Press, 1999)
In Civic Space/Cyberspace Redmond Kathleen Molz and Phyllis Dain assess the current condition and direction of the American public library. They consider the challenges and opportunities presented by new electronic technologies, changing public policy, fiscal realities, and cultural trends. They draw on site visits and interviews conducted across the country; extensive reading of reports, surveys, and other documents; and their long-standing interest in the library's place in the social and civic structure. The book uniquely combines a scholarly, humanistic, and historical approach to public libraries with a clear-eyed look at their problems and prospects, including their role in the emerging national information infrastructure.
Keywords: Public libraries -- United States.; Libraries -- United States -- Special collections -- Computer network resources.; United States.; USA.; elektronické knihy; electronic books